Church - Club: A study in cross programming as a means of survival for the church in the contemporary urban environment - Welz,Thomas Marcel (School of Architecture, Planning and Geomatics, 2016)
This dissertation sets out to discover a new of mode of being for the Pentecostal church which will ensure its survival and continued existence in the contemporary urban environment of the Claremont Central Business District. It is argued that the institution of the church is under threat in the urban context. The church is in decline and urban land is in demand. The dissertation argues cross-programming the church will ensure its survival within this context by introducing new and diverse revenue streams which reduces dependence on dwindling membership contributions, opens up new dialogues between the church and its context, thus justifying its place within the context by filling gaps within and building on the existing contextual programmatic mix. Central to this programmatic problem the space of the church still needs to hold onto and express the essence of what it is that makes it a sacred space. The initial data gathering was done by site, programmatic and statistical analysis; this data was gathered on site and through various publications. In addition, theoretical and technical research was gathered through various peer reviewed texts and publications. In the process of gathering information, common themes, patterns and connections between the different analyses were made which in turn led to further research or conclusions which assisted the argument and informed the design development of the project. In conclusion, it was found that the central idea of cross-programming the urban church was workable. Here there would undoubtedly have to be some compromise as each programme presents different requirements, but ultimately the application of the key theoretical theme of verticality brought unity to the scheme. Additionally, there was also need for some unconventional construction techniques to achieve comfortable internal environments. Finally, the result of the incorporation of diverse programming proved to yield greater and more diverse interactions between the church and its context which ultimately ensures its place, role and survival in the contemporary urban context.